Tunable Energy-Transfer Process in Heterometallic MOF Materials Based on 2,6-Naphthalenedicarboxylate: Solid-State Lighting and Near-Infrared Luminescence Thermometry - Gomez, Germán Ernesto (2020)
Trivalent lanthanide ions (Ln3+) are used to prepare a plethora of coordination compounds, with metal-organic frameworks (MOFs) being among the most sought-after in recent years. The porosity of Ln-MOFs is often complemented by the luminescence imparted by the metal centers, making them attractive multifunctional materials. Here, we report a class of three-dimensional (3D) MOFs obtained from a solvothermal reaction between 2,6-naphthalenedicarboxylic acid (H2NDC) and lanthanide chlorides, yielding three types of compounds depending on the chosen lanthanide: [LnCl(NDC)(DMF)] for Ln3+ = La3+, Ce3+, Pr3+, Nd3+, Sm3+ (type 1), [Eu(NDC)1.5(DMF)]·0.5DMF (type 2), and [Ln2(NDC)3(DMF)2] for Ln3+ = Tb3+, Dy3+, Y3+, Er3+, Yb3+ (type 3). Photoluminescent properties of selected phases were explored at room temperature. The luminescence thermometry capability of Yb3+-doped Nd-MOF was fully investigated in the 15-300 K temperature range under 365 and 808 nm excitation. To describe the optical behavior of the isolated MOFs, we introduce the total energy-transfer balance model. Therein, the sum of energy-transfer rates is considered along with its dependence on the temperature - the sign, magnitude, and variation of this parameter - permitting to afford a thorough interpretation of the observed behavior of the luminescent species of all materials presented here. The combination of novel theoretical and experimental studies presented herein to describe energy-transfer processes in luminescent materials can pave the way toward the design of MOF-based chemical and physical sensors working in an optical range of interest for biomedical applications.